Assessing the comparative feasibility, acceptability and equivalence of videoconference interviews and face-to-face interviews using the time trade-off technique. (September 2022) - Rowen, Donna; Mukuria, Clara; Bray, Nathan; Carlton, Jill; Longworth, Louise; Meads, David; O'Neill, Ciaran; Shah, Koonal; Yang, Yaling
Abstract: This study examines the comparative equivalence, feasibility and acceptability of video and in-person interviews in generating time trade-off (TTO) values. Sample participants in England were recruited using a blended approach of different methods and sampled based on age, gender, ethnicity, and index of multiple deprivation. Participants were randomly allocated to be interviewed either via video or in-person. Participants completed TTO tasks for the same block of 10 EQ-5D-5L health states using the EQ-VTv2 software. Feasibility, acceptability and equivalence was assessed across mode using: sample representativeness; participant understanding, engagement and feedback; participant preferred mode of interview; data quality; mean utility and distribution of values for each health state; and regression analyses assessing the impact of mode whilst controlling for participant characteristics. The video and in-person samples had statistically significant differences in ethnicity and income but were otherwise broadly similar. Video interviews generated marginally lower quality data across some criteria. Participant understanding and feedback was positive and similar across modes. TTO values were similar across modes; whilst mean in-person TTO values were lower for the more severe states, mode was insignificant in most regression analyses. There was no clear preference of mode across all participants, though the characteristics of participants preferring to be interviewed in-person or by video differs. Video and in-person TTO interviews were feasible, acceptable and generated good-quality data, though video interviews had lower quality data across some criteria. Whilst TTO values differed across modes for the more severe states, mode does not appear to be the cause. The study found that the characteristics of people preferring each mode differed, and this should be taken into account in future valuation studies since sample representativeness for some characteristics, and therefore potentially TTO values, could be affected by the choice of mode. Highlights: Both video and in-person TTO interviews were feasible and acceptable. Both produced good-quality data. Video interviews had lower quality data across some criteria. Mode of interview does not appear to cause differences in TTO values. Characteristics of participants preferring video or in-person interviews differ.